(3QSGdI aj GdUhajIs
(3ChdgG (B:s
(3hCeG bSe GdHOGjGJ agh YTQI CHhGH GdjbXI , hGdJhHI hGdeMGSHI hGdEfGHI hGdJacQ hGdJPcQ , hGdEYJUGe s
(3BNQgG (B:s
(3hGdJMbb ef GdZadI hGdfSjGf ef KfGA Ch OYGA Ch QYGA hGdOQLI GdKGfjI Zdi gfG GfJgi bde GdfGSN hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B13s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI eLeO CMeO GdeMGei (B_ (3GdHUQI (B(219 (3N(B) s
Keywords: (3GdeLGejYs